An alternative computation of the entropy of 1D signals based on geometric properties - Bonini, Cristian; Rey, Andrea; Otero, Dino; Amadio, Ariel; García Blesa, Manuel; Legnani, Walter (My University, 2022)
The objective of this work is to present a novel methodology based on the computation of a couple of geometric characteristics of the position of the data points in 1D signal to propose an alternative estimation of signal entropy. The conditions to be fulfilled by the signal are minimal; only those necessary to meet the sampling theorem requirement are enough. This work shows some examples in which the proposed methodology can distinguish among signals that cannot be differentiated by other in-use alternatives. Additionally an original example where the usual ordinal pattern algorithm to compute entropy is not applicable, is presented and analyzed. The proposal developed through this work carries some advantages over other alternatives and constitutes a true advancement in the pathway to compute the distribution function of the sequential points of 1D signals later used to compute the entropy of the signal.
Keywords: Order Pattern Distribution; Permutation Entropy; Symbolic Dynamics; Signal Entropy; Data Points Geometry